Gis Based Flash Flood Hazard Mapping And Selection Of Suitable Sites For Urban Agriculture: The Case Of Bishoftu City, Ethiopia - Kumera, Getu (ASTU, 2023)
One Of The Most Lethal Natural Disasters That Affect Human Existence Is The Flash Flood Hazard (Ffh). It Occurs Frequently, As Soon As Raindrops Fall, And Is Followed By Overflow, Wrecking Homes, Destroying Infrastructure, And Killing Living Creatures. Although Flash Floods Can Happen Anywhere On The Planet, Their Effects Are More Pronounced In Developing Countries Due To A Lack Of Financial Resources, A Lack Of Skill To Design And Put In Place Drainage Systems As Per The Design, Poor Housing Options, Insufficient Early Warning, And Inadequate Readiness. Hence, This Study Has Been Initiated To Analyze And Map GIS-Based Flood Inundation And Locate Suitable Locations For Urban Agriculture (UA) By Combining Different Factors That Serve As Flash Flood Resilience Mechanisms And Selection Of Suitable Sites For Urban Agriculture. Slope, Drainage Density, Elevation, Curve Number, Rainfall, Land-Use/Cover Classes, And Soil Data Were Computed Using Arc GIS Software Platforms. For The Study, The Sentinel-2 Satellite Image, Which Has A 10-Metre Resolution, Was Used For Lulc Classification, While Slope, Elevation, And Drainage Density Data Were Generated From The 12.5-Metre Resolution Of The Alos Palsar Dem, And The Rest Of The Factors Were Collected From The Ethiopian Metrological Institute. To Create Flash Flood Hazard Zones (Ffhs) And An Appropriate Land Map For Urban Agriculture, All The Data Were Regularized And Merged Using A GIS Based On The Analytic Hierarchy Process (Ahp) Technique. The Ffh Model Revealed That Bishoftu City Is Classified As Having Four Different Levels Of Risk: Very High (2106.4ha), High (10464.4ha), Moderate (1444.44), And Low (0.52), With Respective Percentages Of 15.02%, 74.7%, 10.1%, And 0.004%. The Results Of The Study Showed That Many Residential Areas In Bishoftu City, Particularly The Previously Developed Center, Are Vulnerable To Flooding. Following Similar Methods And Analysis Procedures With Ffh, The Results Of The Urban Agriculture Land Model Revealed That Four Land Suitable Classes Were Identified: Highly Suitable (62.38%) (8765.8 Ha), Moderately Suitable (0.02%) (2.8ha), Currently Not Suitable (7.38%) (1037.6ha), And Permanently Not Suitable (30.21%) (4245.5ha) This Indicates That Bishoftu City Is Suitable For Urban Agriculture. In Short, Flood Risk Mapping Is Essential For Raising Public Awareness Of Flood Prone Areas, Demonstrating Susceptibility, Strengthening Financial Capacity, Protecting The Environment, Promoting Environmental Protection Policy, And Assisting First Responders. Because Bishoftu Is Prone To Flash Floods, The Municipality Should Priorities Urban Agriculture Adaptation, Proper Settlement, And Drainage Network Design.
Keywords: Flash Floor, Urban Agriculture, Flood Mapping, Suitability Map